2019
DOI: 10.56093/ijas.v89i6.90834
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive mechanism of stress tolerance in Urochondra (grass halophyte) using roots study

Abstract: An experiment was conducted on Urochondra setulosa (grass halophyte) to explore its survival mechanism under stress conditions. For this, different treatments of salinity/sodicity (pH ~ 9.5, pH ~ 10, ECe ~ 30 dS/m, ECe ~ 40 dS/m and ECe ~ 50 dS/m) were created in micro-plots. Roots are the primary structure that first senses the negative effects of salt stress. So, roots were selected to study the tolerance mechanism. Salinity stress caused higher Na+ accumulation and less reduction in K+ content in comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Here, we have selected two halophytes; Urochondra setulosa and Dichanthium annulatum. Urochondra setulosa is a perennial halophytic grass showing optimum growth up to 500 mM NaCl as reported earlier [8][9][10] and has also been reported to tolerate sea water salinity.…”
Section: Introductionmentioning
confidence: 66%
“…Here, we have selected two halophytes; Urochondra setulosa and Dichanthium annulatum. Urochondra setulosa is a perennial halophytic grass showing optimum growth up to 500 mM NaCl as reported earlier [8][9][10] and has also been reported to tolerate sea water salinity.…”
Section: Introductionmentioning
confidence: 66%
“…It was also noted from the results that S. oleoides accumulated 5.81 mg/g TSS, which decreased to 4.83 mg/g at pH ~ 9.5, 5.23 mg/g and 4.38 mg/g at ECe ~ 15 and 25 dS/m. Stress caused reduction in TSS might serve as a protective molecule and also provide source of energy and carbon (Lata et al 2019) or enhance the activity of hydrolytic enzymes that lead to decreased TSS content (Pooja et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in the current study, sandalwood showed maximum (p ≤ 0.05) production of total soluble sugar with host A. ampliceps. The greater production of specific organic solutes (osmolytes) aids in maintaining the plant water status and photosynthesis as well as safeguarding the cellular machinery against harmful substances (Lata et al, 2019;Kumar et al, 2021). Moreover, during the transfer of nutrients from host to the parasite, potentially hazardous chemicals and disease infections may pass through the haustoria, causing stress in the parasitic plants that contribute to an increase in the production of osmolytes (Zagorchev et al, 2021).…”
Section: Discussionmentioning
confidence: 99%